Anterior segment inflammation and its association with dry eye parameters following myopic SMILE and FS-LASIK - Jian Zhao; Yuan Li; Tianyun Yu; Wenhao Wang; Mutsvene Tinashe Emmanuel; Qianwen Gong; Liang Hu (Annals of Medicine, 2023)
AbstractPurpose To evaluate dry eye and anterior segment inflammation after small incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK), and investigate their association.Methods This prospective and observational study included 96 eyes from 48 myopic patients. The evaluation was performed at baseline, postoperative day 1, week 1, month 1 and month 3. Outcome measures included anterior chamber flare, bulbar redness (BR), limbal redness (LR), ocular surface disease index (OSDI), tear meniscus height (TMH), the first and average noninvasive breakup time (NIBUT-1, NIBUT-a), fluorescein breakup time (FBUT), corneal fluorescein staining (CFS), and Schirmer I. Generalized estimating equations (GEEs) were applied to explore the correlation between flare and ocular surface parameters.Results Flare increased significantly in both groups at day 1 and week 1 and then returned to baseline at month 1. In both groups, BR decreased on day 1 and then gradually increased towards the baseline. In FS-LASIK, LR was lower than baseline at day 1 and month 3. An increase in OSDI was found in the SMILE group on day 1, and in the FS-LASIK group at day 1 to month 1. NIBUT-1 and NIBUT-a decreased significantly on day 1 in both groups. At month 3, NIBUT-a did not return to baseline in FS-LASIK. CFS increased significantly at week 1 in both groups. All parameters were comparable between SMILE and FS-LASIK except for OSDI and NIBUT-a. Time and spherical equivalent showed a correlation with flare.Conclusions Both SMILE and FS-LASIK induced elevated anterior chamber flare and dry eye. However, flare might not be considered a factor determining perioperative dry eye.Key MessagesDry eye disease is common after corneal refractive surgery. Signs and symptoms of dry eye disease persist longer after FS-LASIK compared with SMILE.Both FS-LASIK and SMILE transiently disrupted blood-aqueous barrier integrity, leading to anterior segment inflammation.Anterior chamber flare might not be considered a factor explaining perioperative dry eye, other biomarkers remain for future exploration.